Regression equations to estimate the 2-min walk distance in an adult Asian population aged 40–75 years - Mirza, Fatim; Jenkins, Susan; Justine, M.; Cecins, N.; Hill, Kylie (Wiley-Blackwell Publishing Asia, 2018)
© 2018 Asian Pacific Society of Respirology. Background and objective: There is increased use of the 2‐min walk test (2MWT) to assess functional exercise capacity. However, the distance achieved during this test may be difficult to interpret in the absence of reference values from a local population. Regression equations to estimate the 2‐min walk distance (2MWD) only exist for American and Brazilian populations. The objective of this study was to develop regression equations to estimate the 2MWD in Malaysian adults who were free from major health problems. Methods: Eighty‐seven adults (43 males; mean ± SD age: 57.1 ± 9.6 years) performed two 2MWT using a standardized protocol. Heart rate (HR) was recorded every 30 s during the test. Stepwise multiple regression analysis was performed using age, gender, height, weight and change in HR (ΔHR) as independent variables, and better of the two 2MWD as the dependent variable. A second regression equation, without ΔHR, was planned if ΔHR was retained as one of the predictors of the 2MWD in the first equation. Results: The better of the two 2MWD was 200 ± 34 m. Males walked 33 ± 6 m further than females (P < 0.001). The two regression equations were 196 − 1.1 × age, years + 1.0 × ΔHR, bpm + 31.2 × gender (R2 = 0.73) and 279 − 1.7 × age, years + 35.9 × gender (R2 = 0.47) with females = 0 and males = 1. Conclusion: The equations derived in this study may facilitate the interpretation of the 2MWD in clinical populations in Malaysia, as well as in countries with similar cultural backgrounds to Malaysia.